Property study of ferromagnetic materials for optical media - Lim, Cheng Huat. (2009)
In this work, the properties of ferromagnetic material, TbFeCo was studied. Among all the rare earth transition metals available, TbFeCo is the most popular and widely used in magneto-optical recording.